Comprehensive Income Reporting and Earnings Management - Runita Arum Kanti (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2016)
Purpose. This paper aims to identify the association between comprehensive income reporting and earnings management. More specifically, this study examines whether the implementation of comprehensive income reporting regulations, namely SFAS 130 and ASU 2011-05 is associated with a decrease in earnings management.Design/ methodology. Data for all variables is retrieved from Compustat Global for a nine-year sample of 7962 US firms reporting under International Financial Reporting Standards (IFRS) that provide all the necessary data to conduct the study. The Modified Jones Model is used as a proxy to measure earnings management. Comprehensive income figures are retrieved from Compustat. Recalculated (as-if) numbers are used for firm years prior to the implementation of SFAS 130. While as-reported amounts are used for the years where SFAS 130 has been implemented and also the years during the implementation of ASU 2011-05.Findings. Comprehensive income is found to be significantly negatively associated with earnings management through discretionary accruals. Furthermore, the interaction effects indicate that, after the implementation of SFAS 130 and ASU 2011-05, comprehensive income becomesmore negatively associated with discretionary accruals.Relevance. Other than contributing to the growing literature regarding the usefulness of comprehensive income reporting, this research has implications for the FASB in assessing whether they achieved the target of better comprehensive income reporting.Key words: Comprehensive Income, Earnings management, Interaction effect, Reporting Regulations, SFAS 130, ASU 2011-05.